(untitled) (Research, Society and Development, 2021)
The main objective of this dissertation is to demonstrate the student’s perception regarding the application of ICTs in the classroom as a collaborative mechanism to improve and innovate the learning rite. Based on the data to be obtained, a qualitative comparative analysis will be carried out in order to identify groups that have similar characteristics on the perception of the use of ICTs and assessment systems adopted. A total of 228 university students participated in the study, all of whom were from the city of Natal-RN, with a higher age percentage in the age group of 22 to 29 years, as well as the majority were undergraduates, with a greater concentration of respondents at the beginning of the Science course. Accounting and most private universities. These responded, in addition to socio-demographic and socio-academic data, also the scale of attitudes towards ICTs. Based on the results, the psychometric indicators of the measures used, suggest that the scales are reliable, as well as have great potential for diagnostic analysis of ICT management in academics at public and private universities. In general terms, the results highlight the need for greater attention to the type of course and the period in which the university students are, since it is believed to be an adequate condition for applying ICTs.